FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI PERGERAKAN HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2016-2019 - Achmad Husni Mubaroq; Afifudin Afifudin; Hariri Hariri (Universitas Islam Malang, 2020)
ABSTRACTThis study aims to explain internal factors and external factors that influence stock price movements. The internal factors indicators of this research are Return On Assets (ROA), Debt to Equity Ratio (DER), and Price to Book Value (PBV). The external factors indicators of this study are the Exchange Rate, Inflation, and Interest Rates. The data used is secondary data, obtained from the Investment Gallery of the Faculty of Economics and Business Unisma and the official website www.idx.co.id. Sampling was done using a purposive sampling method. The sample of this research are 40 Manufacturing companies in the 2016-2019 period. Data analysis uses the classic assumption test and multiple linear regression. The results of this study indicate that the ROA and DER independent variables partially do not have a significant effect on stock prices. Whereas PBV, Exchange Rate, Inflation, and Interest Rate partially have a significant influence on stock prices.Keywords: Internal Factors, External Factors, Stock Prices